Apple-Peel intestinal atresia: A systematic review - Francesco Laconi; Charline Bischoff; Theo Michailos; Ongoly Okiemy M'Inserret; Emmanuelle Kremer; Marie-Laurenc (EL-Med-Pub, 2024)
Background: Apple-peel bowel atresia (APA) is rare and thus lacks proper management guidelines. This systematic review analyzes various interventions found in the literature for this type of atresia and highlights the outcomes of each intervention with their complications. Methods: The relevant literature on PubMed, Scopus, Embase, and Cochrane was reviewed from November 2020 to January 2021. Articles published in English, French, Italian, or Spanish between 1990 and 2020, focusing on APA, were included. Data on demography, clinical profile, management provided, time to achieve full feed, length of hospital stay, complications, etc., reviewed. Results: A total of 2495 articles were found, of which only 48 met the inclusion criteria. Among these, 125 patients were treated, with 15 deaths. The most frequently employed intervention was primary resection, with or without tapering, while ostomy creation was less commonly used. The most frequent complication across all techniques appeared to be cholestasis, followed by stenosis of the anastomosis and sepsis. Additionally, there were a total of 7 cases of short bowel syndrome (SBS). Conclusion: The management of apple-peel atresia seems variable in various centers of different countries. The review failed to assess which interventions could lead to faster full enteral feeding. The distal part of the anastomosis must be considered as an active part in the resumption of bowel function.